PENGARUH STRATEGI KOLABORASI MEREK (CO-BRANDING) TERHADAP NIAT PEMBELIAN PADA PRODUK MULTIPURPOSES TINTED SUNSCREEN - Ghina Tamira; Erna Maulina (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
Competition in the beauty sector is very tight at this time requiring BLP and Avoskin brands to be able to compete and be able to maintain and even increase product purchases. Therefore, to answer the existing competition BLP and Avoskin collaborate in the form of co-branding by producing Multipurpose Tinted Sunscreen products. This study aims to determine the effect of co-branding on the purchase intention of Multipurpose Tinted Sunscreen products. The population of this study includes BLP and Avoskin consumers at the official Shopee store with a sample of 120 people. Sampling using non-probability sampling techniques is carried out by purposive sampling. Data analysis was carried out using SPSS with changes to the interval scale with MSI. The results of the analysis show that co-branding has an influence on the purchase intention of Multipurpose Tinted Sunscreen products with a positive influence of 63.1%.